Application of gossypol or gossypol carboxylate in improving performance of perovskite solar cell

By forming gossypol or carboxylic acid gossypol layers in perovskite solar cells, the problems of improved performance and insufficient application of gossypol are solved, performance improvement and stability improvement are achieved, and the application of gossypol is broadened scope.

CN119255625APending Publication Date: 2025-01-03INSTITUTE OF WESTERN AGRICULTURE CAAS
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411363936.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-28
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the prior art, no gossypol is used in optoelectronic devices, especially in terms of performance improvement of perovskite solar cells, resulting in the inability to fully utilize gossypol by-products.

Method used

A layer of gossypol or carboxylic acid gossypol is formed between the electron transport layer of a perovskite solar cell and the perovskite layer. It is made by preparing gossypol or carboxylic acid gossypol solution and coating it on the electron transport layer and annealing Glussypol or carboxylic acid gossypol layer optimizes the performance of perovskite solar cells.

Benefits of technology

The battery performance of perovskite solar cells has been significantly improved, and the stability of gossypol is improved by converting gossypol into carboxylic acid gossypol, broadening the application range of gossypol.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119255625A_ABST
    Figure CN119255625A_ABST
Patent Text Reader

Abstract

The invention discloses an application of gossypol or gossypol carboxylate in improving the performance of a perovskite solar cell, and belongs to the technical field of perovskite cells. A gossypol or carboxylic acid gossypol layer is formed between an electron transport layer and a perovskite layer of the perovskite cell, so that the performance of the perovskite solar cell is improved. According to the perovskite solar cell, the gossypol layer is formed between the electron transport layer and the perovskite layer of the perovskite solar cell, so that the cell performance of the perovskite solar cell can be obviously improved; besides, aiming at the characteristic that the aldehyde group in the gossypol is easy to oxidize, the gossypol is converted into carboxylic gossypol to improve the stability of the gossypol, and then the gossypol is used for forming a carboxylic gossypol layer between the electron transport layer and the perovskite layer of the perovskite solar cell, so that the cell performance of the perovskite solar cell can be further improved. The technical scheme provided by the invention widens the application range of gossypol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of perovskite cells, and specifically relates to an application of gossypol or carboxylic acid gossypol in improving the performance of perovskite solar cells. Background Art

[0002] Cottonpol is a byproduct of the cotton industry and can be used as a drug, but it is not fully utilized due to low demand. Currently, there is no research on the application of cottonpol in optoelectronic devices. Summary of the invention

[0003] The purpose of the present invention is to use gossypol or carboxylic gossypol in improving the performance of perovskite solar cells. By forming a layer of gossypol or carboxylic gossypol between the electron transport layer and the perovskite layer of the perovskite solar cell, the cell performance of the perovskite solar cell can be significantly improved, and the application scope of gossypol can be broadened.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] An application of gossypol or carboxylic gossypol in improving the performance of perovskite solar cells, wherein a layer of gossypol or carboxylic gossypol is formed between the electron transport layer and the perovskite layer of the perovskite solar cell to improve the performance of the perovskite solar cell;

[0006] The CAS number of the gossypol is 303-45-7; the CAS number of the carboxylic acid gossypol is 103276-29-5.

[0007] The structural formulas of gossypol and carboxylic acid gossypol are shown in Formula 1 and Formula 2 respectively:

[0008]

[0009] Preferably, the structure of the perovskite cell comprises a substrate layer, a transparent electrode layer, an electron transport layer, a cottony phenol or cottony phenol carboxylate layer, a perovskite layer, a hole transport layer and a metal electrode layer which are sequentially combined.

[0010] Preferably, the thickness of the cottonpol or carboxylic acid cottonpol layer is 1-50 nm.

[0011] Preferably, the preparation step of the cottonypol or cottonypol carboxylate layer comprises: dissolving cottonypol or cottonypol carboxylate in a solvent to prepare a solution with a concentration of 0.01-10 mg / mL, coating the solution on the electron transport layer, and annealing to obtain the cottonypol or cottonypol carboxylate layer.

[0012] More preferably, the solvent comprises a mixture of one or more of water, DMF, DMSO, tetrahydrofuran, chloroform, ethanol and isopropanol; and the annealing time is 10 s to 10 min.

[0013] Preferably, the raw material of the electron transport layer includes tin dioxide or titanium dioxide.

[0014] Preferably, the raw materials of the perovskite layer include one or more of FAPbBr3, FAPbI3, CsPbBr3, CsPbI3, MAPbBr3, MAPbI3, FAPbCl3, CsPbCl3, MAPbCl3, FASnBr3, FASnI3, CsSnBr3, CsSnI3, MASnBr3, MASnI3, FASnCl3, CsSnCl3, MAPbI3, MAPbBr3, MAPbCl3 and MASnCl3.

[0015] Preferably, the material of the base layer includes glass, polyethylene terephthalate (PET) or polyimide.

[0016] Preferably, the material of the transparent electrode layer includes indium tin oxide (ITO) or fluorine-doped tin oxide (FTO).

[0017] Preferably, the raw materials of the hole transport layer include one or more of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), poly 3-hexylthiophene (P3HT) and poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA).

[0018] Preferably, the material of the metal electrode layer includes aluminum, copper, silver or gold.

[0019] The beneficial technical effects of the present invention are as follows:

[0020] The present invention can significantly improve the battery performance of the perovskite solar cell by forming a cottony phenol layer between the electron transport layer and the perovskite layer of the perovskite solar cell; in addition, in view of the fact that the aldehyde group in cottony phenol is easily oxidized, the cottony phenol is converted into carboxylic acid cottony phenol to improve its stability, and then used to form a carboxylic acid cottony phenol layer between the electron transport layer and the perovskite layer of the perovskite solar cell, which can further improve the battery performance of the perovskite solar cell. The technical solution provided by the present invention broadens the application scope of cottony phenol. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Schematic diagram of the structure of the perovskite solar cell in Examples 1-4 of the present invention; wherein, 1-substrate layer; 2-transparent electrode layer; 3-electron transport layer; 4-gossypol or carboxylic acid gossypol layer; 5-perovskite layer; 6-hole transport layer; 7-metal electrode layer. DETAILED DESCRIPTION

[0022] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0023] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0024] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0025] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0026] The structural schematic diagram of the perovskite solar cell in Examples 1-4 of the present invention is shown in Figure 1 ; Among them, 1-base layer; 2-transparent electrode layer; 3-electron transport layer; 4-gossypol or carboxylic acid gossypol layer; 5-perovskite layer; 6-hole transport layer; 7-metal electrode layer.

[0027] Example 1

[0028] Preparation of perovskite solar cells:

[0029] Dissolve gossypol in water at a concentration of 0.5 mg / mL. Clean the glass substrate covered with indium tin oxide (ITO) in glass cleaner, deionized water, acetone, and isopropanol in turn. Dry with nitrogen and then spin-coat with a 2% dispersion of tin dioxide nanoparticles. The spin-coating speed is 4000 rpm for 30 seconds. Heat at 150°C for 20 minutes and then cool. The thickness of the prepared film is about 30 nm. Spin-coat the gossypol solution onto the tin dioxide film at a spin-coating speed of 4000 rpm for 30 seconds. After spin-coating, heat at 100°C for 5 minutes and then cool. The thickness of the prepared film is about 5 nm. Spin-coat FA with a concentration of 1.5 M 0.95 Cs 0.05PbI3 solution (containing MACl additive at a concentration of 0.15M) was spin-coated at a speed of 4000rpm for 50s. At the 30th second of spin coating, 150μL of chlorobenzene was dropped on the substrate. After spin coating, it was heated at 100℃ for 30min. The thickness of the prepared film was about 500nm. Spiro-OMeTAD chlorobenzene solution with a concentration of 100mg / mL was spin-coated at a speed of 4000rpm for 30s. The thickness of the prepared film was about 100nm. A 100nm thick silver electrode was evaporated to complete the preparation of the perovskite solar cell.

[0030] In AM1.5G, 100mW / cm 2 Measured under simulated sunlight, the initial cell efficiency of the perovskite solar cell prepared in Example 1 was 23.0%, and the cell efficiency was 21.1% after continuous illumination for 100 hours.

[0031] Example 2

[0032] Preparation of perovskite solar cells:

[0033] Dissolve carboxylic acid gossypol in water at a concentration of 0.2 mg / mL, clean the glass substrate covered with fluorine-doped tin oxide (FTO) in glass detergent, deionized water, acetone, and isopropanol in turn, dry with nitrogen, and then spin-coat with a 2% dispersion of tin dioxide nanoparticles at a speed of 4000 rpm for 30 seconds. Heat at 150°C for 20 minutes and then cool. The thickness of the prepared film is about 30 nm. Spin-coat the carboxylic acid gossypol solution onto the tin dioxide film at a speed of 4000 rpm for 30 seconds. Heat at 100°C for 10 minutes and then cool. The thickness of the prepared film is about 3 nm. Spin-coat FA with a concentration of 1.5 M 0.95 Cs 0.05 PbI3 solution (containing MACl additive at a concentration of 0.15M) was spin-coated at a speed of 4000rpm for 50s. At the 30th second of spin coating, 150μL of chlorobenzene was dropped on the substrate. After spin coating, it was heated at 100℃ for 30min. The thickness of the prepared film was about 500nm. Spiro-OMeTAD chlorobenzene solution with a concentration of 100mg / mL was spin-coated at a speed of 4000rpm for 30s. The thickness of the prepared film was about 100nm. A 100nm thick gold electrode was evaporated to complete the preparation of the perovskite solar cell.

[0034] In AM1.5G, 100mW / cm 2 Measured under simulated sunlight, the initial cell efficiency of the perovskite solar cell prepared in Example 2 was 25.0%, and the cell efficiency was 24.2% after continuous illumination for 100 hours.

[0035] Example 3

[0036] Preparation of perovskite solar cells:

[0037] Dissolve carboxylic acid gossypol in ethanol at a concentration of 1 mg / mL. Clean the glass substrate covered with indium tin oxide (ITO) in glass cleaning agent, deionized water, acetone, and isopropanol in turn. After drying with nitrogen, slit-coat a 2% dispersion of tin dioxide nanoparticles at a coating speed of 2 mm / s and a liquid injection speed of 10 μL / s. Heat at 150°C for 20 min and then cool. The thickness of the prepared film is about 30 nm. Coat the gossypol solution on the tin dioxide film by slit coating at a coating speed of 5 mm / s and a liquid injection speed of 10 μL / s. After coating, heat at 100°C for 2 min and then cool. The thickness of the prepared film is about 10 nm. Slit-coat FA with a concentration of 1 M 0.95 Cs 0.05 PbI3 solution (containing MACl additive with a concentration of 0.1M) was coated at a speed of 5mm / s and an injection speed of 20μL / s. After coating the solution, the film was blown dry with nitrogen and then heated at 100°C for 30min. The thickness of the prepared film was about 550nm. PTAA chlorobenzene solution with a concentration of 20mg / mL was slit coated at a speed of 5mm / s and an injection speed of 15μL / s. The thickness of the prepared film was about 80nm. A 100nm thick gold electrode was evaporated to complete the preparation of the perovskite solar cell.

[0038] In AM1.5G, 100mW / cm 2 Measured under simulated sunlight, the initial cell efficiency of the perovskite solar cell prepared in Example 3 was 24.0%, and the cell efficiency was 23.2% after continuous illumination for 100 hours.

[0039] Example 4

[0040] Preparation of perovskite solar cells:

[0041] Dissolve carboxylic acid gossypol in isopropanol at a concentration of 0.8 mg / mL. Clean the glass substrate covered with indium tin oxide (ITO) in glass cleaning agent, deionized water, acetone, and isopropanol in turn. After drying with nitrogen, apply a 2% dispersion of tin dioxide nanoparticles by scraping at a speed of 5 mm / s. Heat at 150°C for 20 minutes and then cool. The thickness of the prepared film is about 30 nm. Apply the gossypol solution to the tin dioxide film by scraping at a speed of 5 mm / s. After coating, heat at 90°C for 2 minutes and then cool. The thickness of the prepared film is about 15 nm. Scrape the FA with a concentration of 1 M 0.95 Cs 0.05PbI3 solution (containing 0.1M MACl additive) was scraped at a speed of 5mm / s. After coating, the solution was blown dry with nitrogen and then heated at 100°C for 30min. The prepared film thickness was about 600nm. P3HT chlorobenzene solution with a concentration of 20mg / mL was scraped at a speed of 5mm / s. The prepared film thickness was about 70nm. A 100nm thick gold electrode was evaporated to complete the preparation of the perovskite solar cell.

[0042] In AM1.5G, 100mW / cm 2 The initial cell efficiency of the perovskite solar cell prepared in Example 4 was measured under simulated sunlight and was 23.5%, and the cell efficiency was 23.1% after continuous illumination for 100 h.

[0043] Example 5

[0044] Preparation of perovskite solar cells:

[0045] Compared with Example 1, the only difference is that gossypol is replaced by carboxylic acid gossypol.

[0046] In AM1.5G, 100mW / cm 2 Measured under simulated sunlight, the initial cell efficiency of the perovskite solar cell prepared in Example 5 was 25.1%, and the cell efficiency was 24.5% after continuous illumination for 100 hours.

[0047] Comparative Example 1

[0048] Preparation of perovskite solar cells:

[0049] Compared with Example 1, the only difference is that the step of preparing the cottony phenol layer is omitted.

[0050] In AM1.5G, 100mW / cm 2 Measured under simulated sunlight, the initial cell efficiency of the perovskite solar cell prepared in Comparative Example 1 was 22.0%, and the cell efficiency was 20.3% after continuous illumination for 100 hours.

[0051] Comparative Example 2

[0052] Preparation of perovskite solar cells:

[0053] Compared with Example 2, the only difference is that the step of preparing the carboxylic acid gossypol layer is omitted.

[0054] In AM1.5G, 100mW / cm 2 Measured under simulated sunlight, the initial cell efficiency of the perovskite solar cell prepared in Comparative Example 2 was 23.0%, and the cell efficiency was 20.9% after continuous illumination for 100 hours.

[0055] Comparative Example 3

[0056] Preparation of perovskite solar cells:

[0057] Compared with Example 3, the only difference is that the step of preparing the carboxylic acid gossypol layer is omitted.

[0058] In AM1.5G, 100mW / cm 2 Measured under simulated sunlight, the initial cell efficiency of the perovskite solar cell prepared in Comparative Example 3 was 22.5%, and the cell efficiency was 20.1% after continuous illumination for 100 hours.

[0059] Comparative Example 4

[0060] Preparation of perovskite solar cells:

[0061] Compared with Example 4, the only difference is that the step of preparing the carboxylic acid gossypol layer is omitted.

[0062] In AM1.5G, 100mW / cm 2 Measured under simulated sunlight, the initial cell efficiency of the perovskite solar cell prepared in Comparative Example 4 was 22.1%, and the cell efficiency was 19.8% after continuous illumination for 100 hours.

[0063] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. An application of gossypol or carboxylic gossypol in improving the performance of perovskite solar cells, characterized in that: Improving the performance of perovskite solar cells by forming a layer of gossypol or carboxylic gossypol between the electron transport layer and the perovskite layer of the perovskite cell; The CAS number of the gossypol is 303-45-7; the CAS number of the carboxylic acid gossypol is 103276-29-5.

2. The use of gossypol or carboxylic gossypol in improving the performance of perovskite solar cells according to claim 1, characterized in that: The structure of the perovskite cell includes a substrate layer, a transparent electrode layer, an electron transport layer, a cotton phenol or carboxylic acid cotton phenol layer, a perovskite layer, a hole transport layer and a metal electrode layer which are sequentially combined.

3. The use of gossypol or carboxylic gossypol according to claim 1 or 2 in improving the performance of perovskite solar cells, characterized in that: The thickness of the cottonpol or carboxylic acid cottonpol layer is 1-50 nm.

4. The use of gossypol or carboxylic gossypol according to claim 1 or 2 in improving the performance of perovskite solar cells, characterized in that: The preparation steps of the cotton pol or carboxylic cotton pol layer include: dissolving cotton pol or carboxylic cotton pol in a solvent to prepare a solution with a concentration of 0.01-10 mg / mL, coating the solution on the electron transport layer, and annealing to obtain the cotton pol or carboxylic cotton pol layer.

5. The use of gossypol or carboxylic gossypol according to claim 1 or 2 in improving the performance of perovskite solar cells, characterized in that: The raw material of the electron transport layer includes tin dioxide or titanium dioxide.

6. Use of gossypol or carboxylic gossypol according to claim 1 or 2 in improving the performance of perovskite solar cells, characterized in that: The raw materials of the perovskite layer include one or more of FAPbBr3, FAPbI3, CsPbBr3, CsPbI3, MAPbBr3, MAPbI3, FAPbCl3, CsPbCl3, MAPbCl3, FASnBr3, FASnI3, CsSnBr3, CsSnI3, MASnBr3, MASnI3, FASnCl3, CsSnCl3, MAPbI3, MAPbBr3, MAPbCl3 and MASnCl3.

7. The use of gossypol or carboxylic gossypol in improving the performance of perovskite solar cells according to claim 2, characterized in that: The material of the base layer includes glass, polyethylene terephthalate or polyimide.

8. The use of gossypol or carboxylic acid gossypol in improving the performance of perovskite solar cells according to claim 2, characterized in that: The material of the transparent electrode layer includes indium tin oxide or fluorine-doped tin oxide.

9. The use of gossypol or carboxylic gossypol in improving the performance of perovskite solar cells according to claim 2, characterized in that: The raw materials of the hole transport layer include one or more of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, poly-3-hexylthiophene and poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine].

10. The use of gossypol or carboxylic gossypol in improving the performance of perovskite solar cells according to claim 2, characterized in that: The material of the metal electrode layer includes aluminum, copper, silver or gold.

Citation Information

Cited By

  • Application of gossypol / TiO2 composite photocatalytic material

    CN120394081A

  • Application of a gossypol / TiO2 composite photocatalytic material

    CN120394081B